2016
DOI: 10.1038/nplants.2016.151
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional cross-kingdom RNAi and fungal uptake of external RNAs confer plant protection

Abstract: Aggressive fungal pathogens such as Botrytis and Verticillium spp. cause severe crop losses worldwide. We recently discovered that Botrytis cinerea delivers small RNAs (Bc-sRNAs) into plant cells to silence host immunity genes. Such sRNA effectors are mostly produced by B. cinerea Dicer-like protein 1 (Bc-DCL1) and Bc-DCL2. Here we show that expressing sRNAs that target Bc-DCL1 and Bc-DCL2 in Arabidopsis and tomato silences Bc-DCL genes and attenuates fungal pathogenicity and growth, exemplifying bidirectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
789
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 617 publications
(818 citation statements)
references
References 52 publications
21
789
1
7
Order By: Relevance
“…Research of HIGS showed that host sRNAs generated by artificial transgenic expression can translocate into colonised pathogen cells to turn down virulence gene expression (Wang et al 2015). In the last few years, HIGS had proven to efficiently control pests, nematodes, filamentous pathogens and parasitic plants (Wang et al 2016). Our latest study described that transgenic cotton plants expressing artificial siRNAs specifically targeting VdH1i gain significant resistance against vascular wilt disease (Zhang et al 2016a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research of HIGS showed that host sRNAs generated by artificial transgenic expression can translocate into colonised pathogen cells to turn down virulence gene expression (Wang et al 2015). In the last few years, HIGS had proven to efficiently control pests, nematodes, filamentous pathogens and parasitic plants (Wang et al 2016). Our latest study described that transgenic cotton plants expressing artificial siRNAs specifically targeting VdH1i gain significant resistance against vascular wilt disease (Zhang et al 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study identified that some Botrytis cinerea sRNAs can hijack host RNAi by binding to host Argonaute 1 (AGO1) to silence Arabidopsis and tomato genes involved in immunity (Weiberg et al 2013). In Arabidopsis and tomato, expressing sRNAs that target B. cinerea DCL gene attenuated fungal pathogenicity and growth (Wang et al 2016). RNAi-deficient Arabidopsis mutants showed affected defence against Verticillium and Fusarium , but not other fungal pathogens including Alternaria brassicicola, B. cinerea and Plectosphaerella cucumerina (Ellendorff et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study suggested that the fungal plant pathogen Verticillium dahliae, the causal agent of Verticillium wilt, also uses pathogen sRNAs (Vd-sRNAs) as effectors, as Vd-sRNAs were found to be loaded into Arabidopsis Argonaute1 (AGO1) during infection. 34 The majority of the predicted host targets of these VdsRNA effectors are putative factors of plant immunity. In addition, animal parasites, such as the gastrointestinal nematode Heligmosomoides polygyrus, also secrete sRNAs via extracellular vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from two different research groups demonstrate fungal control by exogenous application of sRNAs to F. graminearum [53] and B. cinerea [54]. The so-called spray-induced gene silencing (SIGS) might provide novel biotechnological opportunities to control fungal diseases.…”
Section: Rna Silencing and Plant Defence: An Outlookmentioning
confidence: 99%